(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the legal foundations and current development directions of defense system reform in the Republic of Uzbekistan. The research treats defense reform as a law-based governance process rather than a purely military- administrative issue. It examines the Constitution, the Law on Defense, the Defense Doctrine, the Law on the State Border, the Law on Cybersecurity, and recent presidential acts on digital command systems and military regulations. Using formal-legal, systematic and functional methods, the article argues that Uzbekistan’s defense system has evolved from the initial formation of national armed forces into an integrated security model linking military governance, border protection, cybersecurity, professional personnel policy and accountability. Foreign literature on security sector governance is used to assess the relationship between effectiveness, civilian control, legality and human rights. The article concludes that the next stage of reform should focus on legal integration, cyber-resilience standards, competence-based military personnel policy, stronger internal complaint mechanisms and transparent civilian oversight over non-classified aspects of defense policy.